Effects of Family, Type of Personality and Perfectionism on Spouse Selection - Azam Movahedi, (Universiti Kebangsaan Malaysia, 2015)
Introduction: The median age of marriage has raised and its rate has declined in recent years. A suitable spouse is one of the main concerns of everyone’s life, which could be affected by family, personality and society effects on taste and interest of people. This study aimed to investigate the relationship between personality, family and society on spouse selection criteria among college students. Methods: In this cross-sectional study, 250 college students in both gender and study levels were randomly selected. Students were asked to answer validated questionnaires on spouse selection. The obtained data were analyzed by appropriate descriptive and inferential statistical methods using computer software. Results: Results showed that family education has positive significant correlation with education (R2=0.42, p<0.05), religion (R2=0.51, p<0.05), culture (R2=0.38, p<0.05), and manner (R2=0.53, p<0.05) criteria in both genders, while no correlation was found between family’s education and either economic (R2=0.02, p<0.05) or physical criteria (R2=0.1, p<0.05). In addition, male students had significantly higher rate of perfectionism than females (p<0.05). Girls’ priority was good ethical personality, behavioral characteristics, religious beliefs, financial status, education, and beauty respectively, while similarly with minor differences, male priority in spouse selection was good ethical personality, behavioral characteristics, religious beliefs, beauty, education level, and financial situation. The financial situation of girls for men in this study could indicate not only the importance of economic problems in our society, but also greedy wishes, which have been created in recent decades. Conclusions: According to the present study, family and society have more influence than personality on mate selection.